FROM AGROECOLOGY TO DEMOCRATIC RESILIENCE: COMMUNITY-BASED FOOD SECURITY AND CLIMATE ADAPTATION IN WEST SUMATRA - Yulianti, Dina; Setyaka, Virtuous; Bainus, Arry; Sari, Deasy Silvya; Akim, Akim (JWP (Jurnal Wacana Politik), 2026)
The West Sumatra has a high index of food security and because of its dependence on modern farming systems that are chemical based, farmers are susceptible to environmental degradation and market forces worldwide. Through the Critical International Relations (CIR) approach of Robert W. Cox, this paper analyzes how community-based agroecological practices can be the solution to a transition between climate change adaptation and democratic resilience in West Sumatra. The current study is dedicated to the case of Cheap Staple Rice Fields (Sawah Pokok Murah - SPM) an agroecological farming system, a grassroots movement that helps to break free of the company inputs and promotes the self-reliance of farmers. The results demonstrate that SPM does not only lead to climate adaptation and food availability, but also transforms the community-based innovations into the inclusive local governance, in which local governments adopt the grassroots initiatives into their policy-making. This research paper addresses a gap in the literature by demonstrating that food security is not merely associated with the production of adequate food, but also with promoting ecological justice and enhancing the community capacity towards participatory decision-making. Theoretically, the study suggests that agroecology can serve as a deliberative democratic mechanism, allowing local communities to build democratic resilience through daily food governance practices.